Russia vs Ukraine: What Next? (London Journal of Research In Humanities and Social Sciences, 2025)
The reasons for the start of Russia’s war against Ukraine are being discussed. It is shown that it was caused by Moscow’s painful reaction to the collapse of the USSR empire. Due to the lack of complete consensus in the international community regarding the events taking place, the patterns of evolution of world civilization that led to the war are considered from the perspective of the Supersensitive Anthropic Principle (SAP). In particular, it is shown that it was a consequence not only of the collapse of the USSR but also of many preceding events, such as its birth, as well as the birth and demise of Nazi Germany, the fire of World War II, the emergence of the Iron Curtain and the Cold War, and the current confrontation between Russia and the West. All of these are interconnected through a single causal sequence. Its ultimate cause, to a decisive degree, in addition to other objective factors, was the ignorant and deeply flawed utopia of K. Marx, adopted by his Russian followers as an infallible religious doctrine. Nevertheless, in this case, it is not enough to understand the essence of what is happening and its origins. It is even more important to understand the conclusions—the strategy of Russia’s future foreign policy. For it is confident that it is the suzerain among the surrounding vassals. Thinking this way was considered natural a hundred years ago. Today, when humans have reached space and invented nuclear weapons, remaining faithful to the prejudices of the past is unnatural. A misunderstanding of this fact makes Russia’s strategy after the current war unpredictable. However, it is not only the global community but first and foremost the citizens of Russia who need to know what rules of interaction between sovereign countries, distant and nearby neighbors, it intends to follow in the future. The book (I don’t know which is correct: whether it will be a book, a pamphlet, an article, or something else) shows that the choice is limited and that there is less and less time left to make it.